OPTIMIZATION SALINITY AND INITIAL pH ON THE BIOMASS PRODUCTION OF Nannochloropsis sp. K-4 - Arif Sukmawan, I Made; Semadi Antara, Nyoman; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 2 No 1 (2014): Maret, 2014)
This research intended to determine the optimum salinity and initial pH on the growth of Nannochloropsis sp. K-4. The optimization was performed using response surface method (RSM), and central composite design was used to study the effect of salinity and initial pH on the growth of Nannochloropsis sp. K-4. The result showed that the salinity and pH medium of 30.96 ‰ and 8.13 was the optimal condition to grow Nannochloropsis sp. K-4 with biomass yield of 0.41 g/l after 10 days cultivation. Biomass production of Nannochloropsis sp. K-4 was carried out at optimal salinity and initial pH to determine proximate content of the biomass. Proximate analysis of biomass showed that the content of protein, fat, and carbohydrate were 35.55%, 33.66%, and 21.19%, respectively. Keywords: salinity, pH, Nannochloropsis sp. K-4
Keywords: 13